1993
DOI: 10.1007/bf00291988
|View full text |Cite
|
Sign up to set email alerts
|

The sequence-specific nuclear matrix binding factor F6 is a chicken GATA-like protein

Abstract: The sequence-specific DNA-binding protein factor F6, which binds upstream of the cluster of the chicken alpha-globin genes, has previously been found to interact with a DNA fragment containing a replication origin and a nuclear matrix binding site. This protein has been partially characterized. Based on its molecular weight and binding affinity, F6 belongs to a family of GATA proteins, the chicken equivalent of transcription factor NFE-1. An oligonucleotide including the binding site for F6 competes for bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…The importance of MARs in tissue-and cell-type-specific gene expression has been established in model transfection studies and in transgenic animals (71,82). Although specific MAR-binding proteins have been identified (18,77), their role in mediating the tissue-and cell-type-specific binding of active genes to the nuclear matrix is not understood. A number of transcription factors have been found to be associated with the nuclear matrix (6,73,76) and appear to differentially partition between the matrix and an extractable compartment of the nucleus, depending on such variables as tissue type and growth conditions (70).…”
mentioning
confidence: 99%
“…The importance of MARs in tissue-and cell-type-specific gene expression has been established in model transfection studies and in transgenic animals (71,82). Although specific MAR-binding proteins have been identified (18,77), their role in mediating the tissue-and cell-type-specific binding of active genes to the nuclear matrix is not understood. A number of transcription factors have been found to be associated with the nuclear matrix (6,73,76) and appear to differentially partition between the matrix and an extractable compartment of the nucleus, depending on such variables as tissue type and growth conditions (70).…”
mentioning
confidence: 99%
“…From a DNase I-hypersensitive site 14.5 kb upstream of the ir-,aD-, and aA-globin genes (8, 9) to a hypersensitive site 3 kb downstream of the gene cluster, multiple DNA elements such as matrix attachment regions (MARs) (8, 10, 11), topoisomerase II sites (6,8,12), a replication origin (13), enhancers (14-18), and a silencer (17) all thought to represent putative control elements, have been identified, in addition to the promoters of the individual genes (19,20) and repetitive DNA sequences (21). This region seems to be transcribed into a full-domain transcript which spans the entire domain between the most distal DNase I-hypersensitive sites (8,22,23), running right through all the DNA in the area between the external MARs, and also through an internal MAR placed upstream of the first gene.For the present investigation it was important that the positions of MARs (8,10) and topoisomerase II cleavage sites (24) had been mapped in this area and that multiple sites of protein-DNA interaction were identified within the 1.7-kb fragment including the putative origin of replication (13) and a replication-related MAR (10,11,25). We found that nuclease Sl-sensitive regions are located both upstream and downstream of the domain and that, in the upstream area, they coincided with the permanent site of DNA attachment to the nuclear matrix.…”
mentioning
confidence: 99%
“…This domain represents one of the best studied genomic areas in higher eukaryotes in terms of the arrangement of up to 35 kb of DNA elements involved in chromatin structure, mechanisms of transcription, and control of gene expression. From a DNase I-hypersensitive site 14.5 kb upstream of the ir-,aD-, and aA-globin genes (8,9) to a hypersensitive site 3 kb downstream of the gene cluster, multiple DNA elements such as matrix attachment regions (MARs) (8,10,11), topoisomerase II sites (6,8,12), a replication origin (13), enhancers (14)(15)(16)(17)(18), and a silencer (17) all thought to represent putative control elements, have been identified, in addition to the promoters of the individual genes (19,20) and repetitive DNA sequences (21). This region seems to be transcribed into a full-domain transcript which spans the entire domain between the most distal DNase I-hypersensitive sites (8,22,23), running right through all the DNA in the area between the external MARs, and also through an internal MAR placed upstream of the first gene.…”
mentioning
confidence: 99%
“…1C. Several proteins that specifically bind to ARSc, MAR, and SAR DNA have been identified (14,16,18,26,34,45). The similarity of the AT-rich FVIII cDNA sequences to MAR and SAR DNA and the ARSc suggested that the ARSc-and MAR-like sequences in the FVIII cDNA might interact with cellular fac- tors.…”
Section: Resultsmentioning
confidence: 99%